Prevalence of menopausal symptoms and severity related factors among mid-aged Paraguayan women as measured with the 10-item Cervantes Scale - Sandra C. Sánchez-Zarza; Anastasia K. Armeni; Peter Chedraui; Faustino R. Pérez-López; Antonio W.D Gavilanes (Taylor & Francis Group, 2023)
Objective: To determine the prevalence of menopausal symptoms and factors related to severity in mid-aged women.Methods: Cross-sectional study in which 216 urban-living women from Asunción-Paraguay (40-60 years) were surveyed with the 10 item Cervantes Scale (CS-10) and a general questionnaire (personal and partner data).Results: Median (interquartile range [IQR]) age of the sample was 48 [9] years, 48.1% were postmenopausal, 8.8% used menopausal hormone therapy, 39.4% psychotropic drugs, 43.5% had hypertension, 6.5% diabetes, 51.9% abdominal obesity, and 89.3% had a partner (n = 193). A history of sexual abuse was present in 2.8%. Median total CS-10 score was 8.5 [9.75]. Overall, 93.3% (180/193) of women having a partner were sexually active, with a median coital frequency of 8 times per month. According to the CS-10, the three most prevalent menopausal symptoms were: aching in muscles and/or joints (70.8%), anxiety and nervousness (70.8%) and hot flashes/night sweats (54.2%). Factors associated with higher CS-10 scores were: female age and educational level, marital status, menopausal status, and marital sexual aspects. Partner educational level was inversely correlated (rho Spearman coefficient) with CS-10 total scores. However, multiple linear regression analysis found that higher total CS-10 scores (more severe menopausal symptoms) negatively correlated to coital frequency and positively correlated with peri- and postmenopausal status, parity, sedentary lifestyle and a history of sexual abuse.Conclusion: Menopausal symptoms in this mid-aged urban female Paraguayan sample were related to hormonal, sexual and other female aspects.